Using Local and Global Phenomena in Teaching Global Citizenship Education in English at the Elementary Level - Rebecca Rosario Bercasio (RIRAI Publisher, 2023)
This study aimed to enrich Grade 6 English lessons with GCED using local and global issues in the GCED integration in the lessons. Conducted in a public school in the Philippines during the school year 2019-2020, the study used the descriptive method and triangulation method and data sources triangulation. The specific objectives of the study are: (1) Identify phenomena suggested for GCED-enriched Grade 6 English lessons; (2) Develop GCED-enriched lessons in Grade 6 English using a phenomenon-based learning approach; (3) Identify the teaching strategies used in the GCED integration; and (4) Identify the teacher's insights based on his experiences in implementing the lessons. Methods for data collection were documentary analysis of the phenomenon-based GCED-enriched Grade 6 lessons, focus group discussion, workshop, in-depth individual interviews (IDI), analysis of teacher’s reflection notes, and class observations. The suggested phenomena consisted of local and global issues focusing on environmental and climate change, gender and development, identity and diversity, government and politics, and peace and conflict. The grade 6 English lessons can be easily integrated with GCED using local and global phenomena. Varied strategies that are aligned with phenomenon-based learning and active learning can be used for teaching English enriched with GCED. The teacher's insights on the teaching of GCED in Grade 6 English lessons using local and global phenomena can serve as a useful and practical guide in the design and implementation of GCED-enriched lessons. Implementing a whole-school approach to embracing GCED and action options to promote GCED in instructional practices are recommended.